Performance of sulfur/steel slag composite matrix in removing nitrate from surface water with low-carbon content - PENG Xianchun; ZHENG Lili; LU Haoran; WANG Zhefeng; ZHU Zheng; LIANG Wenyan (Gongye shui chuli)
The accumulation of nitrogen pollutants can easily lead to eutrophication of water bodies, and NO3--N is one of the main nitrogen pollutants. A composite matrix of steel slag and elemental sulfur was used for sulfur autotrophic denitrification. SEM was used to observe the surface morphology and microbial adhesion growth on steel slag before and after use. XRD was used to compare the alkalinity difference between steel slag and limestone. Anaerobic bottle batch experiments were conducted to compare the denitrification performance of sulfur/steel slag and sulfur/limestone systems. The effects of mass ratio and dosage on the denitrification performance of sulfur/steel slag systems were explored, and the microbial community structure characteristics before and after sulfur autotrophic denitrification were analyzed. The results showed that steel slag contained abundant alkaline substances such as Ca(OH)2, CaCO3, CaO, MgO, Ca2SiO4, Ca3SiO5, and RO phase. The sulfur/steel slag system had stronger denitrification performance compared to the sulfur/limestone system. When the mass ratio of sulfur/steel slag was 1∶1 and dosages were 20 g, the denitrification effect of the system was the best, and the TN removal rate reached 92.5% on the 10th day, which was higher than 87.4% of the sulfur/limestone system. When the dosage of sulfur and steel slag exceeded 20 g, the system had no significant effect on improving the removal of TN and NO3--N. The analysis of microbial community structure showed that the microorganisms responsible for denitrification belonged to Proteobacteria and Bacteroidota. Compared with the sulfur/limestone system, the microbial diversity in the sulfur/steel slag system was more abundant and the microorganisms were more stable.